If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -4 = u Combine like terms: 5 + -4 = 1 1 = u Solving 1 = u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-1u' to each side of the equation. 1 + -1u = u + -1u Combine like terms: u + -1u = 0 1 + -1u = 0 Add '-1' to each side of the equation. 1 + -1 + -1u = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1u = 0 + -1 -1u = 0 + -1 Combine like terms: 0 + -1 = -1 -1u = -1 Divide each side by '-1'. u = 1 Simplifying u = 1
| 8x-4(40+x)=4 | | 30x-9=21x-53 | | -2n+3+3-7n= | | 3s+12=-6s+6 | | -1.1+u=8 | | 20x-1=4(5x+6) | | 54=(4x-6) | | 4y-8+y=46+3y-4y | | -12+5x=3(x-2) | | b+3b+b+b= | | 5x+6+2x=7x-6 | | 2-a=-8 | | 5x-22+2x=20 | | -29=8+4(c+3) | | 11m-6m=22 | | kn+mp=qforp | | 3(2x-5)=9x+15 | | 40x-15=15x+39 | | 63+(2x+9)=180 | | 2(5x+1)+4=36 | | W+5w+w+w= | | 1.9+3.4=w | | 4x+11x-1=3(5x+9) | | 4x-(3x-1)=-x+12 | | ax-bx=y | | 18-30x-48=-24 | | 40x+4=3x-1 | | -3n^2+11n+28=-4n^2 | | 2x+5y=3y | | x+1*4-11=2x | | 2(x)-y=-65 | | -256a^2+36= |